"May I help you?" – Evaluation of the new student service at the reception desk during the clinical courses at the Department of Operative Dentistry and Periodontology as a part of a longitudinal curriculum of social and communicative competences for dental students - Lichtenstein, Nora (GMS Z Med Ausbild, 2015)
Objectives: Since 2009, the University of Cologne has been developing a longitudinal curriculum for teaching social and communicative skills to dental students (LSK-Dent) based on the recommendations of the Association for Dental Education in Europe (ADEE). As a part of this curriculum it was considered to develop a reception service in the undergraduate treatment courses of the Department of Operative Dentistry and Periodontology involving the organizational and administrative handling of the patients by the students. Students should gain an insight into everyday practice and the reception service should function as a learning environment for social und communicative competences. This article introduces the LSK-Dent project, the implementation of the reception service and presents initial evaluation results. Methods: Patients (n=575) and students (n=53) filled out a questionnaire. Additionally, four semi-structured interviews with students were conducted. Results: The reception service was successfully implemented and endorsed by the students. First indications suggest that the reception service was well received by students as a learning environment for social und communicative competences and viewed as an opportunity to gain an insight into everyday practice. Conclusion: The reception service is an innovative addition to the treatment courses and an example for transforming an already existing reality in a course into a new learning environment for students. To what extent the implementation of reflexive elements can increase the subjectively perceived additional benefit by students, has to be addressed in further studies.